2013
DOI: 10.1111/clr.12237
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled clinical trial to evaluate a new xenograft for alveolar socket preservation

Abstract: No statistically significant difference was observed between TG1 and TG2 after 6 months (P > 0.05), and both biomaterials afforded a more favorable implant position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
59
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 32 publications
(48 reference statements)
0
59
0
1
Order By: Relevance
“…This corresponds to 29-63% of horizontal and 11-22% of vertical bone dimension loss. These volumetric changes often require complementary surgical techniques for the optimal installation of oral implants [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to 29-63% of horizontal and 11-22% of vertical bone dimension loss. These volumetric changes often require complementary surgical techniques for the optimal installation of oral implants [4].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid or limit this ridge modification, several preservation techniques have been described, including the filling of the socket with auto-grafts, allografts, xenografts or alloplastic materials, combined with resorbable or non-resorbable membranes [4]. In a recent systematic review [5], xenografts were found to perform the best, followed by allografts and alloplastic materials when compared to natural healing.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Several grafting techniques and materials combined or not with biological barriers have been suggested to reduce ridge changes after extractions. [4][5][6][7][8][9] Although several of these techniques and materials may limit or reduce resorption, the quality of the newly formed tissue inside the extraction socket may vary widely. 4 Recently, the use of plasma-rich growth factor (PRGF) has been recommended for tissue regeneration in oral surgeries.…”
mentioning
confidence: 99%
“…Osteoblasts are derived from undifferentiated stem-cells and are responsible for the production of bone matrix, rich in collagen (mainly type I) and essential for subsequent mineralization, by adherence of calcium hydroxyapatite crystals, magnesium, potassium, sodium and Carbonate in collagen fibrils [10,20]. Osteoblasts are also rich in alkaline phosphatase, which has a high value in periods of bone formation.…”
mentioning
confidence: 99%
“…Osteoblasts are also rich in alkaline phosphatase, which has a high value in periods of bone formation. The process of formation of new bone mediated by osteoblasts is called osteogenesis [10]. It is known that osteoblasts bind directly to collagen through integrin-RDG (-Arg-Gly-Asp-) sites of interaction.…”
mentioning
confidence: 99%